Incidencia de la red social facebook como medio de publicidad comercial en los pequeños negocios de la ciudad de Babahoyo durante el año 2015 - Almeida Bazán, Kerly Katherine (2016)
This study analyzes the commercial premises, the use of social network Facebook and the importance given to advertising, in order to give managers and owners of the entities an advertising tool, through business platform Facebook obtaining excellent benefits for measurable results there were more than 500 businesses surveyed in this process. Advertising is the way to provide a product through different strategies aimed to induce the purchase, but not before providing the consumer communication elements referred to in the previously defined strategy. In our case specifically, it focuses its actions on the digital platform. Dabble in it, at the mercy of study defined in our research allowed us to discover how commercial businesses in Babahoyo, they could incorporate into its strategy the services offered by Facebook. Since the world knew the benefits of this platform, it has experienced rapid growth, to the point of being considered one of the most accepted by society. In our country, specifically in Babahoyo this situation can be considered a niche market to which the author sees in his research.